The roles of ICT telecommunication infrastructure on foreign direct investment in Malaysia - Kui Ming Tiong; Ming Yu Cheng; Chee Keong Choong (Asian Academy of Management Journal, 2022)
The development of the digital economy and the emergence of new technologies are changing the way of doing business. In recent foreign direct investment (FDI) studies, factors in addition to conventional ownership-location-internalisation (OLI) factors have been explored to enrich the FDI model. This study looks at the roles of information and communications technology (ICT) telecommunication infrastructure on FDI in Malaysia. The two-step system generalised method of moments (GMM) approach is used. To overcome the limitations of the dynamic panel model on the “small groups” problem, this study uses five three-year average data for the period between 2002 to 2016, and the Windmeijer finite-sample correction, the robust standard errors for estimation. The results show a significant positive role of mobile telephony on FDI. Besides, institutional factors are found to have significant impacts on FDI. The findings indicate the importance of the institutional framework and ICT telecommunication infrastructure, which can be jointly used with the OLI paradigm to explain factors driving FDI in the new economy.